2004
DOI: 10.1083/jcb.200407182
|View full text |Cite
|
Sign up to set email alerts
|

Condensed mitotic chromatin is accessible to transcription factors and chromatin structural proteins

Abstract: During mitosis, chromosomes are highly condensed and transcription is silenced globally. One explanation for transcriptional repression is the reduced accessibility of transcription factors. To directly test this hypothesis and to investigate the dynamics of mitotic chromatin, we evaluate the exchange kinetics of several RNA polymerase I transcription factors and nucleosome components on mitotic chromatin in living cells. We demonstrate that these factors rapidly exchange on and off ribosomal DNA clusters and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
154
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(177 citation statements)
references
References 73 publications
(95 reference statements)
18
154
5
Order By: Relevance
“…In contrast to our findings, H1.2-GFP was solely located on chromatin during the cell cycle in transfected HeLa cells (34) and NIH 3T3 cells (32). Possibly, there are differences between the binding and phosphorylation of H1.2-GFP and the native H1.2 but the most likely explanation for this difference is that the residence time for H1.2 bound to chromatin is too short to become captured by formaldehyde crosslinking during fixation in accordance with recent results (35).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, H1.2-GFP was solely located on chromatin during the cell cycle in transfected HeLa cells (34) and NIH 3T3 cells (32). Possibly, there are differences between the binding and phosphorylation of H1.2-GFP and the native H1.2 but the most likely explanation for this difference is that the residence time for H1.2 bound to chromatin is too short to become captured by formaldehyde crosslinking during fixation in accordance with recent results (35).…”
Section: Discussioncontrasting
confidence: 99%
“…Alterations in chromatin binding characteristics between the native protein and its GFP-labeled counterpart have recently been recognized in HMGN proteins (36). In addition, the rate of H1.2-GFP recovery after photobleaching was higher at metaphase compared with prophase, anaphase or telophase, indicating that the rate of dynamic exchange of H1.2-GFP increased during metaphase (32), in line with our present results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, this modulation is one of the key mechanisms essential for the functional role of nuclear hormone receptors (Stenoien et al, 2001;Schaaf and Cidlowski, 2003;Stavreva et al, 2004;Elbi et al, 2004b;Farla et al, 2005;Rayasam et al, 2005). In vivo FRAP has been used to study the dynamic properties of chromatin proteins and that the FRAP recovery kinetics of chromatin proteins are directly related to their chromatin-binding properties (Lefebvre et al, 1991;Fragoso et al, 1998;Lever et al, 2000;Kimura and Cook, 2001;Kimura et al, 2002;Maruvada et al, 2003;Phair et al, 2004;Becker et al, 2005;Chen et al, 2005). Because BRG1 and BRM were selectively recruited to the MMTV array in response to hormone (Figures 2 and 3), we used FRAP to study the binding kinetics of chromatin-remodeling complexes at the amplified MMTV target in vivo.…”
mentioning
confidence: 99%
“…This may be due to shifting regulatory molecules and exposing transcription factor binding sites on DNA. It has been demonstrated that although mitotic chromatin is condensed, transcription factors are still able to bind to their target sites 15 and this may provide a hitherto untested explanation for the enhancement of reprogramming associated with mitotic transition.…”
Section: Deubiquitination Of Mitotic Chromatin Enhances Reprogrammingmentioning
confidence: 99%